Kopje (model 210 - Mosa) met logo Arbeidsbureau en bijbehorende witte schotel (BG K22/515), model 223 Mosa
Kopje (model 210 - Mosa) met logo Arbeidsbureau en bijbehorende witte schotel (BG K22/515), model 223 Mosa.